Photoelastic models applied to dental restorations - Marín-Miranda, Miriam (2021)
Objective: To improve the understanding of the changes generated by restorative procedures through photoelastic models. Dental reconstruction should be based on principles of occlusion in order not to cause premature contact points during preparation and restoration procedures that can lead to disorders such as occlusal trauma, TMJ dysfunction, or fractures. This paper presents a didactic method to objectively visualize occlusal loads and their distribution. Materials and methods: Photoelastic models of teeth and maxillary segments were made to visualize the effects of dental preparations and restorations, as well as the wear of premature contact points. Results: The direction, intensity and distribution of stresses in the crown and bone support were analyzed by photoelasticity. Conclusions: The technique allows us to visualize how the structures are affected from the cavity preparation, the different stresses with diamond or carbide burs, in addition to observing how a premature contact point not only affects the organ that contains it but also the surrounding structures.